2015
DOI: 10.1891/0047-2220.46.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Does the Purpose for Using a Service Dog Make a Difference in the Perceptions of What it Takes to Create Successful Outcomes in the Workplace?

Abstract: The objective of this article is to determine if there are perceptual differences regarding the importance of elements deemed imperative for successful service dog partnerships in the workplace (Glenn, 2013) between those who have experience with dogs for mobility/stability and those for medical alert/response. Thirty individuals completed this online survey (mobility/stability: n = 18; medical alert/response: n = 12). Participants rated the importance of elements in response to the question, “How important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The use of independent samples t-tests to examine the cluster averages of subgroups is common among group concept mapping studies, with a number of recently published studies employing the technique. 4648 Consistent with these studies, we used a Welch’s t-test, which assumes unequal variances and unequal sample sizes, to test the differences in cluster means between identified subgroups. For example, male and female mean cluster ratings were compared for each of the individual clusters generated in the model.…”
Section: Methodsmentioning
confidence: 99%
“…The use of independent samples t-tests to examine the cluster averages of subgroups is common among group concept mapping studies, with a number of recently published studies employing the technique. 4648 Consistent with these studies, we used a Welch’s t-test, which assumes unequal variances and unequal sample sizes, to test the differences in cluster means between identified subgroups. For example, male and female mean cluster ratings were compared for each of the individual clusters generated in the model.…”
Section: Methodsmentioning
confidence: 99%
“…This experience may have created a positive trait-based stereotype (Blair & Banaji, 1996) – that is, those with a legitimate disability are proactive and open in communicating about their disability. However, previous research suggested individuals with invisible disabilities may be more concerned about privacy and, therefore, less likely to disclose their disability (Glenn & Thorne, 2015). Contributing to signaling theory, evidence shows that most HR practitioners in this study indicated skepticism that a previously undisclosed mental health condition was severe enough to be a disability or that the individual needed the disability-AA (Buhai, 2016; Mills, 2017).…”
Section: Discussion Of Implicationsmentioning
confidence: 99%
“…After obtaining informed consent, 60–75-min video-recorded interviews were conducted and transcribed by the principal investigator. A semistructured interview protocol was used to guide the discussion, which was informed by previous research with disability-AA handlers, service animal trainers and counselors, but it was adapted according to the organizational perspective (Ju, Pacha, Moore, & Zhang, 2014; Foreman et al , 2017; Glenn & Thorne, 2015; Mills, 2017). Interviews began with introductions and requests for demographic information about the organization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations